2012
DOI: 10.1128/jb.06740-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Biochemical, and Molecular Characterization of the Polypeptide Transport-Associated Domain of Escherichia coli BamA

Abstract: The BamA protein of Escherichia coli plays a central role in the assembly of ␤-barrel outer membrane proteins (OMPs). The Cterminal domain of BamA folds into an integral outer membrane ␤-barrel, and the N terminus forms a periplasmic polypeptide transport-associated (POTRA) domain for OMP reception and assembly. We show here that BamA misfolding, caused by the deletion of the R44 residue from the ␣2 helix of the POTRA 1 domain (⌬R44), can be overcome by the insertion of alanine 2 residues upstream or downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…If a mutant BamA protein fails to correctly assemble itself or other ␤-barrel OMPs, including the lipopolysaccharide (LPS) transporter LptD, then cells expressing the mutant BamA protein may have a compromised outer membrane permeability barrier resulting in vancomycin and rifampin sensitivity. Consistent with this view, we have recently reported a BamA POTRA domain mutant with increased sensitivity toward vancomycin and rifampin (36). Because cells expressing BamA AAA or BamA ⌬RGF grow best on glycerol minimal medium at 30°C (Fig.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…If a mutant BamA protein fails to correctly assemble itself or other ␤-barrel OMPs, including the lipopolysaccharide (LPS) transporter LptD, then cells expressing the mutant BamA protein may have a compromised outer membrane permeability barrier resulting in vancomycin and rifampin sensitivity. Consistent with this view, we have recently reported a BamA POTRA domain mutant with increased sensitivity toward vancomycin and rifampin (36). Because cells expressing BamA AAA or BamA ⌬RGF grow best on glycerol minimal medium at 30°C (Fig.…”
Section: Resultssupporting
confidence: 60%
“…The folding status of BamA was assessed by conducting the heat modifiability test, in which the correctly folded form of BamA is distinguished from the unfolded (denatured) form based on the faster mobility of the former on an SDS-polyacrylamide gel (16,28,29,36). As expected, wild-type BamA was correctly folded, as no slowly migrating (denatured) species was present in the unheated envelope sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble N-terminal end of BamA folds into five polypeptide-transport-associated (POTRA) domains [23] whose structure revealed possible interactions with substrate polypeptides via β-augmentation [24-26]. Mutational and pull-down assays have also revealed that the POTRA domains of BamA are critical for interactions with the Bam lipoproteins [24] and a periplasmic chaperone, SurA [27,28]. Thus, the POTRA domains appear to serve as the initial staging ground for substrate interaction and folding.…”
Section: Introductionmentioning
confidence: 99%
“…The Cterminal domain of BamA forms a transmembrane 16-stranded β-barrel core, while the Nterminal region of BamA forms five soluble periplasmic polypeptide-transport-associated domains (POTRA) (Jansen et al, 2015b, Kim et al, 2007, Gatzeva-Topalova et al, 2010, Gatzeva-Topalova et al, 2008. These POTRA domains contribute to BamA stability and directly interact with BamBD within the periplasm, nascent polypeptides and the periplasmic chaperone SurA (Bennion et al, 2010, Kim et al, 2007, Workman et al, 2012, Dong et al, 2012a. The lipoproteins BamC and BamE interact directly with BamD (Kim et al, 2011a, Malinverni et al, 2006, Wu et al, 2005, Stenberg et al, 2005.…”
Section: The β-Barrel Assembly Machine (Bam) Complexmentioning
confidence: 99%